A Preliminary Study on Public Health Implications of Avian Tuberculosis in Selected Districts of the Oromia Region, Ethiopia - Tesfaye Debelu; Fufa Abunna; Gezahegne Mamo Kassa (Veterinary Medicine International)
Background. Avian tuberculosis is a zoonotic disease which remains a problem in extensive poultry production systems under which chickens scavenge for survival in unhygienic environments. Methodology. A cross-sectional study was conducted from November 2016 to June 2017 at high-land areas of Gerar Jarso and Ada’a and Boset districts located at mid and low altitudes of Oromia, Ethiopia, respectively, to assess the perception of farmers on the occurrence of avian tuberculosis in chickens and its public health implications using a semistructured questionnaire. Result. The study evidenced poor awareness of the farmers, as only 11% (10/91) of them had well-perceived occurrence of the disease in chickens and its risk of zoonosis. Conclusion. Hence, it revealed that there is poor public perception on the occurrence as well as public health implications of avian tuberculosis, demanding further studies for verification and technical interventions.